2013
DOI: 10.1007/s12311-013-0517-4
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning

Abstract: Behavioral studies have demonstrated that both medial prefrontal cortex (mPFC) and cerebellum play critical roles in trace eyeblink conditioning. However, little is known regarding the mechanism by which the two brain regions interact. By use of electrical stimulation of the caudal mPFC as a conditioned stimulus, we show evidence that persistent outputs from the mPFC to cerebellum are necessary and sufficient for the acquisition and expression of a trace conditioned response (CR)-like response. Specifically, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…In support of this speculation, presenting the cerebellum with basilar pontine nuclei mossy fiber inputs, whose temporal patterns mimic the persistently active neurons in the mPFC, is necessary for the expression of trace CR-like responses in rabbits [11]. Moreover, we have recently shown evidence that direct persistent inputs from the mPFC to the cerebellum are sufficient for the acquisition and expression of trace CR-like responses in guinea pigs [35], providing additional support to the preceding speculation.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In support of this speculation, presenting the cerebellum with basilar pontine nuclei mossy fiber inputs, whose temporal patterns mimic the persistently active neurons in the mPFC, is necessary for the expression of trace CR-like responses in rabbits [11]. Moreover, we have recently shown evidence that direct persistent inputs from the mPFC to the cerebellum are sufficient for the acquisition and expression of trace CR-like responses in guinea pigs [35], providing additional support to the preceding speculation.…”
Section: Introductionsupporting
confidence: 76%
“…Indeed, the caudal mPFC is necessary for the acquisition [18,20] and expression [21,22] of trace CRs, whereas the rostral mPFC is implicated for the extinction [19]. Moreover, it has been suggested that persistent outputs from the caudal mPFC to the cerebellum can provide a possible neural mechanism for bridging the time gap between the CS and the US, thereby contributing to the acquisition [35] and the expression [11,25] of trace CRs. In contrast, activations of the rostral mPFC are reported to inhibit the expression of CRs but not their acquisition [55,56], suggesting that the rostral mPFC acts as a potent inhibitor of reflex eyeblinks.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of mPFC cells showed phasic response patterns to the CS that are not capable of supporting cerebellar learning for the trace interval used in the current study (Kalmbach et al 2009; see also Chen et al 2014). To determine whether the increased robustness of persistent responses observed between the second halves of ACQ1 and ACQ2 was specific to persistent cells, the same bootstrap analysis was applied to mPFC cells that showed phasic responses.…”
Section: Resultsmentioning
confidence: 93%
“…In rabbits, the cerebellum and mPFC are necessary to learn and express trace eyeblink CRs (Kalmbach et al 2009;KronforstCollins and Disterhoft 1998;Siegel and Mauk 2013;Solomon et al 1986; see also Chen et al 2014 andTakehara et al 2003), whereas the role of the hippocampus is restricted to the acquisition phase (Kim et al 1995;Moyer et al 1990;Solomon et al 1986). Because the cerebellum requires near overlap of the CS and US to support learning (Chen et al 2014;Kalmbach et al 2010), the hypothesized role of the mPFC in trace conditioning is to provide a CS-evoked input to the cerebellum (via the pons) that persists across the stimulus-free trace interval to overlap with the US (Fig. 1A, bottom; Chen et al 2014;Kalmbach et al 2009;Siegel et al 2012;Weiss and Disterhoft 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation